2011
DOI: 10.1089/pho.2009.2737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Photobiomodulation on Collagen IV During Skeletal Muscle Tissue Remodeling After Injury in Rats

Abstract: The collagen IV content is modulated in regenerating skeletal muscle under LLLT, which might be associated with better tissue outcome, although the histologic analysis did not detect tissue improvement in the LLLT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 28 publications
3
35
0
4
Order By: Relevance
“…However, there was a decrease in the collagen concentration at day 13 post-surgery after 50 J/cm 2 laser irradiation. The effects of LLLT on collagen metabolism are still unclear (Baptista et al 2011). Some authors have suggested that lasertherapy increases collagen synthesis (Yeh et al 1989;Reddy et al 1989) whereas other authors have demonstrated a decrease in collagen synthesis (Pereira et al 2002;Marques et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there was a decrease in the collagen concentration at day 13 post-surgery after 50 J/cm 2 laser irradiation. The effects of LLLT on collagen metabolism are still unclear (Baptista et al 2011). Some authors have suggested that lasertherapy increases collagen synthesis (Yeh et al 1989;Reddy et al 1989) whereas other authors have demonstrated a decrease in collagen synthesis (Pereira et al 2002;Marques et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The healing of an injured skeletal muscle follows a fairly constant pattern divided in three phases: destruction phase (characterized by the rupture and ensuing necrosis of the myofibres and formation of a haematoma and an inflammatory cell reaction), repair phase (consisting of the phagocytosis of the necrotised tissue, regeneration of the myofibres and production of a connective tissue scar) and remodelling phase (a period during which the maturation of the regenerated myofibres, retraction and reorganization of the scar tissue and recovery of the functional capacity of the muscle occurs) (Järvinen et al 2007) Although muscle tissue is a dynamic tissue with an excellent capacity for repair after the injury, such a process is considered slow and some injuries might even affect muscle functioning, leading to atrophy, contracture, pain and increased likelihood of re-injury (Renno et al 2007;Baptista et al 2011). In this context, there is a need to develop the treatments able to accelerate muscle cell proliferation and preventing fibrosis during the healing process, which would decrease the rehabilitation time and the regenerative processes, producing a return to the previous level of function as quickly and thoroughly as possible (Markert et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Em adição, Baptista et al 25 , que utilizaram a criolesão em músculo tibial anterior de ratose tratamento com laser de baixa potência (660 nm, 5 J/cm 2 , 10 segundos), verificaram que este recurso proporcionou um aumento de coláge-no tipo IV nos 7 primeiros dias, sem interferir na duração do processo de reparo, sendo a regeneração muscular também evidenciada após 21 dias, tanto no grupo tratado quanto no submetido apenas a lesão, em concordância com os presentes achados da avaliação morfológica. Verzola et al 17 utilizaram a natação para verificar a influência no remodelamento de miocárdio de ratos e evidenciaram benefícios desta terapia por meio de aumento na atividade da metaloprotease de matriz tipo 2 (MMP2).…”
Section: Discussionunclassified